OFR-146(7)-77 Comparative Coal Transportation Costs: An Economic And Engineering Analysis Of Truck, Belt, Rail, Barge And Coal Slurry And Pneumatic Pipelines ? Volume 7 Pneumatic Transport ? 7.1 Introduction - Michael Rieber (The National Institute for Occupational Safety and Health (NIOSH), 1977)
A new mode of coal transportation based on the principles of pneumatic conveying has been recently, proposed by Soo, et al. [5]. Pneumatic transport is not a novel concept and commercial experience with pneumatic pipelines for short haul distances is plentiful. The list of applications is long and includes transporting ores, chemicals and pharmaceutical products, agricultural products, and domestic and industrial wastes. The study by Soo, et al. [5] updated an earlier one [l0] and presented the most recent economic evaluation of pneumatic transportation of coal. Their preliminary study concluded that there are immediate advantages for short-distance transport (less than 100 miles) and that it is both technologically and economically feasible. That study also concludes that pneumatic transport has a higher potential and more promising profitability in long-distance applications than rail if new track and roadbed must be built. Some of the advantages of long and short distance pneumatic pipeline transport of coal compared to rail and slurry transport are: 1) Replacement of diesel fuel consumed by unit trains, as the pipeline can be powered by coal-generated electricity; 2) Reduction of the skilled-labor costs required for upgrading and maintaining railroads; 3) Elimination of signaling, rerouting and overpass costs due to increased rail traffic on' mainline trackage;